INVESTIGATION ON AUTONOMOUS PESTICIDE SPRAYING ROBOTIC VEHICLE IN AGRICULTURE FIELD - Mr.Manikandan Ganesan, Mrs.Ishwarya K. R, Mr. Demoz Lisanework, Mr.Ayenachew Hailu Mengiste (International Journal of Modern Agriculture, 2021)
As we all aware that the Agriculture is an extremely important in our developing countries like India. In earlier times crops got infected with insects and other factors in less amount. but today crops are affecting with several diseases and insects, so pesticides are sprayed by manpower to crops. The time required to spray is long and it is not possible to cover a full field with human power. Here we found a solution to spray the crops with less time and efficiently at low cost. This proposed work is to bring an autonomous robot that can spray the pesticides to the crops without any side effects on farmers. In this work an autonomous robot is developed to save the crops and pesticides.